Postural control, falls and Parkinson's disease: Are fallers more asymmetric than non-fallers? - Barbieri, Fabio Augusto [UNESP]; Carpenter, Mark; Beretta, Victor Spiandor [UNESP]; Orcioli-Silva, Diego [UNESP]; Simieli, Lucas [UNESP]; Vitório, Rodrigo [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Elsevier, 2019)
Postural control asymmetry is an important aspect of Parkinson's disease (PD) that may be associated with falls. The aim of this study was to compare the postural control asymmetry during postural tasks between fallers and non-fallers in people with PD and neurological healthy age-matched controls (CG). Individuals with idiopathic PD (n = 24) and CG (n = 24) were sub-divided into groups of fallers and non-fallers based on their fall history over the past year. Participants performed blocks of three 30-s trials of quiet standing with feet in a side-by-side and semi-tandem stance position. The center of pressure parameters for each limb were measured and used to calculate the symmetry index. Fallers compared to non-fallers had decreased asymmetry of vertical force in the side-by-side condition. During the tandem-front leg condition, PD non-fallers increased asymmetry of the medial-lateral velocity of sway compared to CG non-fallers. In addition, for the tandem–back leg condition, PD non-fallers increased asymmetry of total displacement and medial-lateral root mean square and mean velocity of sway compared to PD fallers. The results of the study did not support the hypothesis that PD fallers are more asymmetric than PD non-fallers. On the contrary, our results indicated that PD non-fallers had higher postural control asymmetry, especially during the more challenging (semi-tandem standing) postural task.
Keywords: Asymmetry; Fall; Human movement; Parkinson's disease; Posture